Masyarakat post-teologi : wajah baru agama dan demokratisasi Indonesia - Rumadi, 1970- (Bekasi : Gugus Press, 2002)
New concepts on the implementation of Islamic religious teachings and democracy in Indonesia; collected articles
Includes index
Keywords: Islam -- Indonesia; Democracy -- Religious aspects -- Islam; Islam and politics -- Indonesia